American Alligator Ecology and Monitoring for the Comprehensive Everglades Restoration Plan - Ken G. Rice; Frank J. Mazzotti (EDIS)
The American alligator once occupied all wetland habitats in south Florida, from sinkholes and ponds in pinelands to freshwater sloughs to mangrove estuaries. Nearly all aquatic life in the Everglades is affected by alligators (Beard, 1938). As a top predator in their ecosystem, they undergo an extraordinary change in body size and consume different prey items as they grow. As ecosystem engineers, the trails and holes that alligators build provide refuge for wading birds and fish during the dry season, and their nests provide elevated areas for nests of other reptiles and germination of plants less tolerant of flooding. This document is Cir 1478, one of a series of the Wildlife Ecology and Conservation Department, University of Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences. Publication date: November, 2005.